Complications of Renal Failure and Toxoplasma gondii Infection on Some Biochemical Parameters of a Patient with COVID-19 - Jabbar Mushattat Sukayna; Ali Faieq Zahraa; Radhi AbdulHussein Jabbar Amer; Majid Almusawi Malak; Abadi Mohammed Jabbar (BIO Web of Conferences)
This study was designed for infection with T. gondii by using specific IgG and IgM by VIDAS technique to indicate T. gondii. The experiment was distributed into three groups: (A) (N=30) kidney failure patients group, (B) (N=30) patients with kidney failure patients and COV-19, (C) (N=30) patients with covid- 19 + kidney failure and T.gondii infected. The criteria were studied Blood Urea (B.U.) mg\dl, Serum Creatinine (S.Cr.) mg\dl, Albumin serum (ALB) mg\dl, Total serum protein (T.S.P) and phosphate test (PO4) mg\dl. The examination of the parameters mentioned above was performed using a spectrophotometer device by wavelength 490-540 nm. It was seen that the amounts of creatinine, PO4, and blood urea were significantly higher (P < 0.05) in COVID-19-infected patients with renal failure than in the control group of patients with renal failure. However, it was noted that patients with COVID-19 and kidney failure, as well as T. gondii infection, demonstrated a return to normal blood urea levels. Creatinine and phosphorous oxyhydroxide levels were not different between those with COVID-19 + renal failure and those with T.gondii infection (P > 0.05).